Improving estimates of transmission capital costs for utility-scale wind and solar projects to inform renewable energy policy. (December 2019) - Gorman, Will; Mills, Andrew; Wiser, Ryan
Abstract: Estimating the overall costs of transmission needed to integrate variable renewable energy (VRE) onto the grid is challenging. An improved understanding of these transmission costs would support electricity system planning as VRE penetrations increase. This paper brackets VRE transmission capital costs using multiple approaches based on interconnection studies, actual transmission projects, capacity-expansion simulation models, and aggregated U.S. VRE-related transmission expenditures. Each approach possesses advantages and drawbacks, and combining the approaches lends confidence to the results. The resulting range of average levelized VRE transmission costs is $1–$10/MWh, which is generally lower than earlier estimates in the literature. These transmission capital costs can increase the direct plant-level levelized cost of VRE by 3%–33%, based on levelized costs of energy of $29–$56/MWh for utility-scale wind and $36–$46/MWh for utility-scale solar. As VRE deployment continues to expand, policy makers can use this information to (1) assess the benefits of transmission avoidance and deferral when comparing distributed energy resources versus utility-scale projects, (2) evaluate the potential costs of large-scale public transmission investments, and (3) better analyze system-level costs of utility-scale VRE technologies. Future research can expand on the framework presented here by providing a review of operation and maintenance costs for transmission systems. Highlights: Estimating the cost of transmission to integrate renewable energy is challenging. We use interconnection, actual project, and simulation data to bound cost estimate. The average levelized transmission capital cost for renewable energy is $1-$10/MWh. The costs contextualize the benefits of transmission avoidance/deferral in policy. Policy makers can use costs to evaluate public transmission investments.